2015
DOI: 10.1073/pnas.1507793112
|View full text |Cite
|
Sign up to set email alerts
|

Design and structure of two HIV-1 clade C SOSIP.664 trimers that increase the arsenal of native-like Env immunogens

Abstract: A key challenge in the quest toward an HIV-1 vaccine is design of immunogens that can generate a broadly neutralizing antibody (bnAb) response against the enormous sequence diversity of the HIV-1 envelope glycoprotein (Env). We previously demonstrated that a recombinant, soluble, fully cleaved SOSIP.664 trimer based on the clade A BG505 sequence is a faithful antigenic and structural mimic of the native trimer in its prefusion conformation. Here, we sought clade C native-like trimers with comparable properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
120
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 43 publications
5
120
0
Order By: Relevance
“…6B). We also found that, unexpectedly, the 2G12 affinity column could be used to purify the CZA97.012 SOSIP.664-His proteins, an observation similar to ones made with other trimers based on different clade C env genes (64). The explanation may be rooted in promiscuous glycan recognition, where the lack of a glycan from certain bNAb epitopes, including 2G12, can be compensated for by the presence of another glycan (46,47).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…6B). We also found that, unexpectedly, the 2G12 affinity column could be used to purify the CZA97.012 SOSIP.664-His proteins, an observation similar to ones made with other trimers based on different clade C env genes (64). The explanation may be rooted in promiscuous glycan recognition, where the lack of a glycan from certain bNAb epitopes, including 2G12, can be compensated for by the presence of another glycan (46,47).…”
Section: Resultssupporting
confidence: 74%
“…The present versions of the 92UG037.8 and CZA97.012 SOSIP.664 trimers are fully closed, highly thermally stable and have antigenic properties consistent with their native-like appearance when visualized by negative-stain EM. These trimers therefore add to the repertoire of such reagents that are now available for structural and immunogenicity studies (6,18,28,64).…”
Section: Discussionmentioning
confidence: 99%
“…The recent high-resolution structure of the BG505 SOSIP trimer reinvigorated efforts to develop an HIV vaccine as it elicits tier 2 neutralizing serum antibodies in preclinical models (16-21). We developed two other SOSIP trimers, the HIV subtype B JRFL-and subtype C 16055-derived trimers which require negative selection to yield homogenous, well-ordered trimers (22), and other clade B and C SOSIPs are also now available (23,24). Subsequently, we designed a different means to covalently link the subunits, creating cleavage-independent native flexibly linked (NFL) trimers that do not require precursor cleavage.…”
mentioning
confidence: 99%
“…It has therefore been proposed that elicitation of broadly neutralizing responses may require the use of polyvalent formulations of SOSIP Envs based on diverse viral variants to accomplish the hallmark goal of breadth and potency. Envs from different isolates, however, vary widely in their propensities to form recombinant NL trimers using the SOSIP design (35,36). Consequently, numerous purification methods have been developed to isolate NL trimers from lower-yield Envs (26,35,36,37,43).…”
mentioning
confidence: 99%